Older Australians can adhere to a traditional Mediterranean style diet over two weeks: a pilot dietary intervention study. Issue 1 (December 2015) - Davis, Courtney; Bryan, Janet; Hodgson, Jonathan; Wilson, Carlene; Murphy, Karen
Abstract Background Consumption of a Mediterranean diet (MedDiet) is associated with several significant health benefits, however most evidence comes from Mediterranean countries, where the diet may be more culturally acceptable. Whether older Australians can adhere to a traditional MedDiet is unknown. We aimed to test the feasibility of elderly Australians adhering to a MedDiet over two weeks. Methods Male (n = 4) and female (n = 6) omnivorous Australians aged ≥65 years living in metropolitan Adelaide were recruited and completed the study during June-July, 2013. Participants followed their habitual diet for one week (Habitual diet phase), then a MedDiet for two weeks (MedDiet phase). The intervention diet was rich in plant foods and extra virgin olive oil, moderate in dairy foods and seafood, and low in red meat and added sugars. Adherence to the MedDiet was measured through a semi-quantitative daily food checklist. Dietary intake was assessed by weighed food records (WFRs) and food frequency questionnaires (FFQ) during both phases to monitor dietary compliance and nutrient intake. A feasibility survey assessed barriers to following the diet. Height was measured at baseline; body mass at baseline, and at the end of each phase. Cohen's d effect sizes were calculated for differences between nutrient intakes during the Habitual diet and MedDiet phases. Means ± SD are presented for continuous variables. Results Daily food checklists show adherence to the MedDiet was 87 %. Both WFRs and FFQs indicated that participants increased their intakes of total and monounsaturated fat, ratio of monounsaturated fat to saturated fat, fibre and vitamin C. Seven of 10 participants felt they could continue following the diet long term. Barriers to compliance included palatability of plain Greek yoghurt, limited red meat, limited variety within the diet and length of meal preparation. Conclusion This population of older Australians were able to follow a MedDiet over two weeks and most believed they could follow it longer-term. Minor adjustments to recommendations for dairy foods, poultry, small goods and discretionary foods would improve adherence. After modifications, the MedDiet will then be used in a larger, randomised controlled intervention trial. Trial registration Australia and New Zealand Clinical Trials Registry (ANZCTR):ACTRN12613000636752